2010
DOI: 10.1007/s10389-010-0360-8
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of outpatient palliative care in Germany—a survey among office-based physicians

Abstract: Background: Currently, Palliative care is widely discussed. Aim of this study is to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The best cooperation is seen with caregivers, but cooperation with psycho-social care providers should be improved. Studies are requested that focus on the collection of longitudinal data for more comprehensive insight (Prenzler et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The best cooperation is seen with caregivers, but cooperation with psycho-social care providers should be improved. Studies are requested that focus on the collection of longitudinal data for more comprehensive insight (Prenzler et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, various facilitators or barriers in the practices were identified, i.e. the absence of a nominated contact person for caregivers or a lack of cooperation with a nursing service [ 34 ]. Supporting or inhibiting factors associated with caregivers were also identified, i.e.…”
Section: Resultsmentioning
confidence: 99%